Endoskopische Interventionen in der Pneumologie = Endoscopic interventions in pulmonology - Gompelmann, Daniela; Herth, Felix (Der Internist, 2016)
Bronchoscopy plays a significant role in the diagnosis and treatment of pulmonary diseases. Hemoptysis, or central airway obstruction, is a common indication for interventional bronchoscopy. In addition, the treatment of early lung cancer is the domain of bronchoscopy in inoperable patients. In recent years, endoscopic techniques have also been established as new therapeutic options in advanced chronic obstructive pulmonary disease and uncontrolled bronchial asthma.
Paralleltitel von Frontdoor übernommen
Gesehen am 21.11.2018